1997
DOI: 10.1128/aem.63.1.289-295.1997
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Two Functional Forms of Intracellular Protease PfpI from the Hyperthermophilic Archaeon Pyrococcus furiosus

Abstract: The hyperthermophilic archaeon Pyrococcus furiosus grows optimally at 100؇C by the fermentation of peptides and carbohydrates. From this organism, we have purified to homogeneity an intracellular protease, previously designated PfpI (P. furiosus protease I) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…4). Preferred amino acids of the P1 site for DJ-1 protease are Val, Ile and Ala, which are non-polar amino acids, and these phenomena are similar to those for Pfpi [28]. Optimal pH for DJ-1 protease was 5.5-6.0 and its activity decreased at more alkaline pH (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…4). Preferred amino acids of the P1 site for DJ-1 protease are Val, Ile and Ala, which are non-polar amino acids, and these phenomena are similar to those for Pfpi [28]. Optimal pH for DJ-1 protease was 5.5-6.0 and its activity decreased at more alkaline pH (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, this value seems to be still too high for a protease. Studies performed on the PfPI (a protease extracted from the hyperthermophilic archaebacteria Pyrococcus furiosus ) showed that PfPI protease has a behavior similar to PPA [14, 15]. PfPI protease has a monomeric form of 18.8 kDa oligomerising into a form of 200 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…So far, three proteases have been characterized from P. furiosus. These are a membrane-associated serine protease (48), an intracellular protease with trypsin-and chymotrypsin-like activities (28,29), and an intracellular endopeptidase that cleaves at prolyl residues (30). In addition, two proteases have been purified from other members of the family Thermococcales, including a thiol protease from an unclassified species of Pyrococcus (40) and a serine protease from Thermococcus stetteri (33).…”
mentioning
confidence: 99%